Phytochemical Screening and In-vitro Antioxidant Profiling of Solvent Fractions of Canna edulis Ker Gawler - Mishra, Tanmayee; Das, Abhaya Prasad; Sen, Arnab (Free Radicals and Antioxidants)
Introduction: Canna edulis Ker Gawler, grown in the sub Himalayan region containing starchy rhizome are used by the tribal people as food and herbal medicine. Methods: Investigations were done to find out 2,2-diphenyl-1-picryl hydrazyl (DPPH) radical scavenging activity, total flavonols and total proanthocyanidin contents, nitric oxide (NO) scavenging activity, hydroxyl radical scavenging activity of different solvent fractions of aquous extract of C. edulis rhizome. Among the cellular molecules, lipids containing unsaturated fatty acids with more than one double bond are particularly susceptible to action of free radicals. The resulting reaction, known as lipid peroxidation and anti lipid peroxidation activity has been performed using goat liver homogenate. Results: Six out of 29 fractions showed DPPH free radical inhibition above 75% and were used for further phytochemical screening. Diethyl ether : ethyl acetate (1:3) fraction showed the maximum inhibition percent. Highest amount of total flavonol and total proanthocyanidins were recorded in diethyl ether : ethyl acetate (1:3) fraction. Maximum NO scavenging activity and hydroxyl radical inhibition activity were observed in bioactive diethyl ether : ethyl acetate (1:1) fraction. Inhibition of lipid peroxides was maximum in ethyl acetate fraction. Data from thin layer chromatography (TLC) revealed the presence of phenolic compounds in all fractions, whereas flavonoid glycoside compounds were restricted in ethyl acetate and diethyl ether : ethyl acetate (1:3). Conclusions: Thus it can be concluded that the antiradical scavenging activity of Canna rhizome may be due to the presence of polyphenolic compouns like phenols, flavonoids, proanthocynidins etc.
Keywords: Anti-lipid peroxidation; Canna; column chromatography; DPPH; polar